Analisis Pemilihan Model Decline Curve Analysis untuk Estimasi Penurunan Produksi pada Reservoir Shale Gas - Fadhil, Muhammad; Rahman, Muhammad Rizqie Fathan; Rivani, Mukhlis Farhan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Determining a production decline model is a critical step in analyzing the performance of Shale Gas reservoirs, which exhibit complex fluid flow characteristics. This study aims to identify the most appropriate Decline Curve Analysis (DCA) model and estimate the rate of production decline based on historical data. The data used including production rates, time, and cumulative production were obtained from Mazher Ibrahim and processed using Microsoft Excel. The methods employed include exponential, hyperbolic, and harmonic models using curve-fitting approaches and evaluation of the coefficient of determination (R²). The analysis results indicate that the hyperbolic model is the best fit, with a decline factor (b) of 0.6 and a decline rate (D) of 2%. These values indicate that the production decline is moderate and relatively stable.